Toot & Puddle : I'll be home for Christmas - Hobbie, Holly (Boston : Little, Brown and Company, 2001)
Delayed by a snowstorm, Toot gets unexpected help getting back to Woodcock Pocket in time to celebrate Christmas with Puddle.
School Library Journal
Pub Weekly
Booklist
2.7
K-3
Keywords: Christmas -- Fiction; Blizzards -- Fiction; Pigs -- Fiction; Christmas -- Fiction; Blizzards -- Fiction; Pigs -- Fiction